The Impact of Section 302 and 404(b) Internal Control Disclosures on Prospective Investors' Judgments and Decisions: An Experimental Study. Issue 2 (1st March 2016) - Church, Bryan K.; Schneider, Arnold
Abstract : This paper reports the results of an experiment designed to investigate participants' reaction to quarterly and annual internal control disclosures. Quarterly disclosures include managers' disclosure of no control deficiencies, a significant deficiency, or a material weakness. Annual disclosures include the auditors' opinion on internal control, which either affirms managers' earlier disclosure or reveals new information. We find that participants react negatively to the disclosure of a material weakness, as might be expected. Participants invest less in a target company when internal control is ineffective rather than effective. By comparison, participants do not react negatively to the disclosure of a significant deficiency. Indeed, we find that they react positively to such disclosure accompanied by a clean (unqualified) audit opinion on internal control. Subsequent analyses indicate that participants' investment decisions are affected by their assessments of the reliability of financial statements and the credibility of management.